Advances in the Study of Plant-Derived Vesicle-Like Nanoparticles in Inflammatory Diseases - Tan X; Xu Y; Zhou S; Pan M; Cao Y; Cai X; Zhao Q; Zhao K (Journal of Inflammation Research, 2023)
Xuejun Tan,1 Yukun Xu,1 Sirui Zhou,1 Mingyue Pan,1 Yue Cao,1 Xiuping Cai,2 Qing Zhao,1,2,* Kewei Zhao1,2,* 1The Third Clinical Medical College, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 2Guangzhou Key Laboratory of Chinese Medicine Research on Prevention and Treatment of Osteoporosis, The Third Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kewei Zhao; Qing Zhao, Department of Laboratory Medicine, The Third Affiliated Hospital of Guangzhou University of Chinese Medicine, 261 Longxi Avenue, Liwan District, Guangzhou, Guangdong, People’s Republic of China, Tel +86-13711355225 ; +86-18825144487, Email zkw2011@gzucm.edu.cn; zhaoqing900116@126.comAbstract: All humans are universally affected by inflammatory diseases, and there is an urgent need to identify new anti-inflammatory drugs with good therapeutic benefits and minimal side effects to the organism. Recently, it has been found that plant-derived vesicle-like nanoparticles (PDVLNs) have good biocompatibility, with their active ingredients exhibiting good therapeutic effects on inflammation. They can also be used as drug carriers for targeted delivery of anti-inflammatory drugs. Therefore, PDVLNs represent a popular research area for novel anti-inflammatory drugs. This paper details the origin, biological functions, isolation and purification, and identification of PDVLNs, as well as the therapeutic effects of their intrinsic bioactive components on inflammatory diseases. It also introduces their targets as drug carriers to facilitate the development and application of PDVLNs anti-inflammatory drugs.Keywords: plant, vesicle-like nanoparticles, inflammation, inflammatory diseases